India and East Africa : new opportunities in healthcare cooperation - Chaturvedy, Rajeev Ranjan (2020)
As maritime neighbours, India and the countries of East Africa have a long history of trade relations, as well as cultural and educational exchange. The current COVID- crisis has thrown up huge prospects for Indian-East African engagement, particularly to strengthen healthcare cooperation.